Bifurcations of the normal modes of the Ne...Br2 complex (2009)
ABSTRACT: We study the classical dynamics of the rare gas-dihalogen Ne· · ·Br2 complex in its ground electronic state. By considering the dihalogen bond frozen at its equilibrium distance, the system has two degrees of freedom and its potential energy surface presents linear and T-shape isomers. We find the nonlinear normal modes of both isomers that determine the phase space structure of the system. By means of surfaces of section and applying the numerical continuation of families of periodic orbits, we detect and identify the different bifurcations suffered by the normal modes as a function of the system energy. Finally, using the Orthogonal Fast Lyapunov Indicator (OFLI), we study the evolution of the fraction of the phase space volume occupied by regular motions. Keywords: Bifurcations, Br2 complex, Orthogonal Fast Lyapunov Indicator (OFLI), Potential energy surface.